2017
DOI: 10.1007/s11356-017-0891-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of government regulations on Manufacturer’s behaviors under carbon emission reduction

Abstract: This paper shifts the discussion of low-carbon technology from science to the economy, especially the reactions of a manufacturer to government regulations. One major concern in this paper is uncertainty about the effects of government regulation on the manufacturing industry. On the trust side, will manufacturers trust the government's commitment to strictly supervise carbon emission reduction? Will a manufacturer that is involved in traditional industry consciously follow a low-carbon policy? On the profit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…In addition, due to administrative divisions, the promotion of officials, and local competition, the division and cooperation of the regional industrial chain are increasingly limited in the administrative region. However, the positive effects precipitated by manufacturing agglomeration and industrialization have not spread across the provinces in the Yangtze River Economic Belt [61]. In the process of industrial structure adjustment on the east coast, excess industries have transferred to central and western regions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…In addition, due to administrative divisions, the promotion of officials, and local competition, the division and cooperation of the regional industrial chain are increasingly limited in the administrative region. However, the positive effects precipitated by manufacturing agglomeration and industrialization have not spread across the provinces in the Yangtze River Economic Belt [61]. In the process of industrial structure adjustment on the east coast, excess industries have transferred to central and western regions.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Therefore, manufacturers and processing plant must adopt cleaner production technology while implementing BPS (Liu et al, 2015;Shi et al, 2010). Moreover, the government should implement emissions control measures, such as carbon cap and trade, to influence the operational strategies of manufacturers and processing plants through emission monetization to achieve a win-win situation of environmental and economic benefits (Feng at al., 2019;Jian et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Choi et al (2018) and Wang et al (2019) explored how the stochastic risk preference of retailers affects the values of quick response to the supply chain and its members. Feng et al (2019) formalized the game's theoretic model of manufacturers associated with governments in a low-carbon technology market and derived the mixed strategy Nash equilibrium. Ye et al (2019) introduced the environmental governance cost prediction and showed that different risk coefficients have a greater impact on the investment in environmental governance.…”
Section: Behavior Strategy Selection Of Stakeholdersmentioning
confidence: 99%